Inventing Canada : early Victorian science and the idea of a transcontinental nation - Zeller, Suzanne Elizabeth, 1952- (Heritage., 1987)
Tapping a wide range of archival and published sources, Suzanne Zeller documents the place of Victorian science in British North American thought and society during the era of Confederation.